2022
DOI: 10.1029/2021tc007166
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Rift Systems and Their Fault Networks in Response to Surface Processes

Abstract: Continental rifting is responsible for the generation of major sedimentary basins, both during rift inception and during the formation of rifted continental margins. Geophysical and field studies revealed that rifts feature complex networks of normal faults but the factors controlling fault network properties and their evolution are still matter of debate. Here, we employ high‐resolution 2D geodynamic models (ASPECT) including two‐way coupling to a surface processes (SP) code (FastScape) to conduct 12 models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 100 publications
4
16
0
Order By: Relevance
“…We do not exclude that the end of low‐angle faults activity may be related to a limit to the relationship between fault offset and serpentinization (Boddupalli et al, 2022). But in agreement with observations (Lymer et al, 2019) and numerical modelling (Neuharth et al, 2022) at the Galicia margin and at the P detachment, we suggest that low‐angle faults locked‐up when they moved further away from the locus of extension, such as illustrated in our model (Figure 6c,d).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We do not exclude that the end of low‐angle faults activity may be related to a limit to the relationship between fault offset and serpentinization (Boddupalli et al, 2022). But in agreement with observations (Lymer et al, 2019) and numerical modelling (Neuharth et al, 2022) at the Galicia margin and at the P detachment, we suggest that low‐angle faults locked‐up when they moved further away from the locus of extension, such as illustrated in our model (Figure 6c,d).…”
Section: Discussionsupporting
confidence: 93%
“…The potential mantle temperature for the southern segments of the Porcupine Basin where the PMR developed (Figure 1a), southwest of the study area, have been suggested to range from 1290° to 1450°C (Calvès et al, 2012), which may be too hot for mantle serpentinization whose maximum temperature is debated but may be between 350°C (Bickert et al, 2020) and 600°C (Lavier & Manatschal, 2006). However, mantle temperature during rifting of the northern magma‐poor segment where the P detachment developed is not defined, and recent numerical modelling indicates that serpentinization can occur in hyper‐extended, magma‐poor rift segments with low syn‐rift sedimentation (Liu et al, 2022; Neuharth et al, 2022), such as in the study area. Serpentinization also occurs at MORs where the extensional systems mix both tectonic spreading and magmatic accretion (Escartin et al, 2017; Haughton et al, 2019; Peirce et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We acknowledge that the approach presented in Reeve et al ( 2022) may have been driven by mathematical models suggesting regional stratigraphic unconformities as representative of the geodynamic processes causing continental breakup. There are several examples of these models in the recent literature (Korchinski et al, 2021;Neuharth et al, 2022;Pérez-Gussinyé et al, 2020). Such models are often formulated assuming sedimentation rates that are relatively constant across and along continental margins, and sediment sources that are homogeneous in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the current version incorporates surface processes, imposing rates of erosion and sedimentation on the top of the free surface (Silva & Sacek, 2022). Recently, other thermomechanical codes available for the scientific community incorporated the interaction with surface processes (e.g., Beucher & Huismans, 2020;Neuharth et al, 2022) taking into account the simulation of fluvial and hillslope processes. In the present version of Mandyoc, only predefined erosion/sedimentation rate (variable in space and time) is possible.…”
Section: Statement Of Needmentioning
confidence: 99%